Brief Report: Food Insufficiency Is Associated With Lack of Sustained Viral Suppression Among HIV-Infected Pregnant and Breastfeeding Ugandan Women. (1st March 2016) - Koss, Catherine A.; Natureeba, Paul; Nyafwono, Dorcas; Plenty, Albert; Mwesigwa, Julia; Nzarubara, Bridget; Clark, Tamara D.; Ruel, Theodore D.; Achan, Jane; Charlebois, Edwin D.; Cohan, Deborah; Kamya, Moses R.; et al.
Abstract : Abstract: Food insecurity is associated with poor virologic outcomes, but this has not been studied during pregnancy and breastfeeding. We assessed sustained viral suppression from 8 weeks on antiretroviral therapy to 48 weeks postpartum among 171 pregnant and breastfeeding Ugandan women; 74.9% experienced food insufficiency. In multivariable analysis, food insufficiency [adjusted odds ratio (aOR) 0.38, 95% confidence interval (CI): 0.16 to 0.91], higher pretreatment HIV-1 RNA (aOR 0.55 per 10-fold increase, 95% CI: 0.37 to 0.82), and lopinavir/ritonavir versus efavirenz (aOR 0.49, 95% CI: 0.24 to 0.96) were associated with lower odds of sustained viral suppression. Interventions to address food security may improve virologic outcomes among HIV-infected women. Abstract : Supplemental Digital Content is Available in the Text.